Development of Test Management System Quality Assurance in Space Venturo Applications: Pengembangan Test Management System Quality Assurance Pada Aplikasi Space Venturo - Yekti Asmoro Kanthi; Muhammad Mutawalli Sya’rawi; Hilman Nuril Hadi (Universitas Muhammadiyah Sidoarjo, 2023)
The development of a Test Management System for Quality Assurance in the Space Venturo application is the focus of this research. In order to optimize performance within the development team, it is crucial to have an application that can effectively manage and facilitate task delegation, scheduling, and collaboration among team members. The existing project management application, Space Venturo, lacks the necessary features to ensure quality assurance processes and the storage of relevant information regarding product testing. Therefore, this study aims to enhance the functionality of Space Venturo by incorporating a Test Management System. This system is intended to simplify. Highlights: Streamlined Task Delegation: Efficiently assign and track testing tasks among team members to ensure a systematic QA process. Enhanced Collaboration: Foster improved communication and coordination within the development team, facilitating knowledge sharing and issue resolution. Comprehensive Information Storage: Create a centralized repository for relevant testing data, ensuring easy access and retrieval of essential product testing information Keywords – test management system, quality assurance, space venturo